Kajian Sosio-Teologis mengenai Dasa Titah (Keluaran 20:1-17) dan Relevansinya di Era Kontemporer - Gian Gideon Akin (Voice, 2021)
Rules, laws and prohibitions were made to direct human life. For a nation, this is important as a way of life that must be applied by its people. God made the covenant with the Israelites like a deal. Through Moses, God gave all the laws which were the conditions of the agreement to the nation of Israel.On this journal, the author will describe how the Ten Commandments brought a feeling of truth to the social life of the Israelites and obedience to that covenant.The purpose of the author in this article is to find an understanding of the Ten Commandments, find out how the Israelites responded when accepting the agreement, discover how the Ten Commandments played a role in the survival of the nation of Israel, especially the relationship with God and others and find principles that can be applied by each believers in this contemporary era.